2003
DOI: 10.1177/105678790301200403
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a High School in Open Enrollment Areas: Voices of Israeli Parents and Children

Abstract: Advocates of school choice reform in education believe that when parents are granted the right to choose their child's school, they will act rationally, in a goal-oriented fashion, to maximize their educational utility by finding the "best" school for their children. The current qualitative study aims to examine these basic assumptions by exploring the elements that comprise the process of school choice, thereby unearthing the reasons for choosing or rejecting a school. Based on data gathered from eight famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For example, an Israeli study revealed that families went to these events in at least two schools (Oplatka, 2003). In England, students intending to leave secondary education found further education institutions' open evenings to be most important single information source (Foskett & Hemsley-Brown, 2001).…”
Section: School Marketing and Promotional Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, an Israeli study revealed that families went to these events in at least two schools (Oplatka, 2003). In England, students intending to leave secondary education found further education institutions' open evenings to be most important single information source (Foskett & Hemsley-Brown, 2001).…”
Section: School Marketing and Promotional Activitiesmentioning
confidence: 99%
“…Past research has supported some of the theoretical observations indicated above, pointing to the centrality of the open evening in the schoolchoice process. For example, an Israeli study revealed that families went to these events in at least two schools (Oplatka, 2003). In England, students intending to leave secondary education found further education institutions' open evenings to be most important single information source (Foskett & Hemsley-Brown, 2001).…”
Section: School Marketing and Promotional Activitiesmentioning
confidence: 99%
See 1 more Smart Citation